2022
DOI: 10.14715/cmb/2022.68.4.18
|View full text |Cite
|
Sign up to set email alerts
|

Insecticidal effect of Eucalyptus globulus and Rosmarinus officinalis essential oils on a stored food pest Ephestia kuehniella (Lepidoptera, Pyralidea)

Abstract: For the purpose of evaluating the local heritage of eastern Numidia, an ethnobotanical survey was conducted on a population located in the province (department) of El-Tarf (North-East of Algeria) on a frequency of use of two plants known in traditional health; Eucalyptus globulus (Myrtaceae) and Rosmarinus officinalis (Lamiaceae). After processing data, our results show a female dominance when using these plants on a fairly advanced age group (40 to 60 years old). These plants are used by the people at their f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 27 publications
0
1
0
Order By: Relevance
“…The insecticidal effect has been studied in numerous species of different orders. Significant results were obtained for the species: the lesser grain borer, Rhyzopertha dominica, with E. microtheca essential oil-LC 50 at 24 h being 25.261 µL/L of air and significantly decreased to 18.995 µL/L at 72 h [115]; for stored food pest Ephestia kuehniella (Lepidoptera, Pyralidea) with E. globulus oil-LC 50 = 0.013 and LC 95 = 0.081 µL/cm 2 [122]; for the Mediterranean fruit fly, Ceratitis capitata (Diptera: Tephritidae), with the oil of E. cinerea-LC 50 = 0.028 µL/insect, and LC 90 = 0.373 µL/insect [123]. With E. campaspe Moore and E. torquata Luehm.…”
mentioning
confidence: 99%
“…The insecticidal effect has been studied in numerous species of different orders. Significant results were obtained for the species: the lesser grain borer, Rhyzopertha dominica, with E. microtheca essential oil-LC 50 at 24 h being 25.261 µL/L of air and significantly decreased to 18.995 µL/L at 72 h [115]; for stored food pest Ephestia kuehniella (Lepidoptera, Pyralidea) with E. globulus oil-LC 50 = 0.013 and LC 95 = 0.081 µL/cm 2 [122]; for the Mediterranean fruit fly, Ceratitis capitata (Diptera: Tephritidae), with the oil of E. cinerea-LC 50 = 0.028 µL/insect, and LC 90 = 0.373 µL/insect [123]. With E. campaspe Moore and E. torquata Luehm.…”
mentioning
confidence: 99%
“…Another recent study on Tunisian R. officinalis EOs also found eucalyptol (37.56%) and camphor (7.10%) as the principal components [41]. Similarly, Rekioua [38] reported eucalyptol (37.51%) and camphor (11.70%) as the major chemical components in Algerian R. officinalis samples. Other studies have reported different levels of major components, with eucalyptol (25.5%), isobornyl acetate (15.7%), and camphor (12.2%) being the main components of EO obtained from R. officinalis grown in the United Arab Emirates [42], while two different EOs obtained from R. officinalis grown in Palestine contain three main components, namely eucalyptol (4.81-37.83%), α-pinene (13.07-51.36%), and camphor (11.95-24.30%) [43].…”
Section: Cg-ms Analysismentioning
confidence: 77%
“…The chemical composition of R. officinalis EO has been the focus of numerous studies, which have investigated samples collected from various locations and at different phenological stages, both in Algeria and around the world [38,39]. In this study, we examined the chemical composition of EO extracted from R. officinalis grown in Algeria.…”
Section: Cg-ms Analysismentioning
confidence: 99%
“…Plant inventory of the sampling area. Taibi et al, 2018;Boumendjel et al, 2021;Rekioua et al, 2022), thus adding quality to the honey harvested.…”
Section: Plant Inventory Of the Regionmentioning
confidence: 99%